Soren Kierkegaards Existentialism: A Study on the Way of Enjoying Life during Post Truth Era - Saputra, Riki; Ritonga, Mahyudin; Arrasyid, Arrasyid (Insaniyat: Journal of Islam and Humanities, 2024)
This study aims to explain the means of deriving enjoyment in life during the Post-Truth era by drawing upon the existentialist values of Soren Kierkegaard. A qualitative approach with a conceptual design was adopted using exploratory, interpretative, and analytical methods. The results showed that individuals were able to derive enjoyment from life during the Post-Truth Era by embracing the following Soren Kierkegaard's existentialism values. First, being oneself; living under the narrative of the heart and mind. Second, being moral; and adhering oneself to universal rules. Third, living a religious life; having a direct connection with God, and being critical of religion. The significance of Soren Kierkegaard's existentialism lies in its emphasis on individuality, freedom, and the search for authentic meaning in life. Kierkegaard's philosophy highlights the importance of subjectivity and individual responsibility in facing a life full of decisions. His concept of existential decision-making stresses conscious choices that reflect awareness and accountability. emphasizing the uniqueness of individuals and the pursuit of life's meaning. This philosophical perspective underscores the critical role of self-awareness, self-development, and personal responsibility in leading a meaningful life. Kierkegaard believes that humans must become authentic selves, which continue without stopping. This is a struggle that must be carried out at all times, so that humans can become the subjects of their lives. Becoming an authentic self is a task that must be held accountable, and individuals have the possibility to realize the enjoyment of life. In Kierkegaard's thought, life is natural and sometimes has a greater sense of significance than life that is not natural. The natural way of life for humans is the way of enjoying life described by Kierkegaard.